Genomic insight into the integrative conjugative elements from ICEHpa1 family - Sun, Huarun; Zhang, Junkai; Miao, Qingqing; Zhai, Yajun; Pan, Yushan; Yuan, Li; Yan, Fengbin; Wu, Hua; Hu, Gongzheng (Frontiers in Veterinary Science, 2022)
Integrative conjugative elements (ICEs) are important carriers for disseminating resistance genes. We have previously reported a novel element ICEHpa1 carrying seven antibiotic resistance genes, which could be self-transmissible relying on the novel T4SS. To identify novel ICEHpa1 variants from 211 strains and novel T4SS encoded in ICEHpa1, and to explore the relationships in these ICEs, four complete sequences of ICEs were identified by WGS analysis and antimicrobial susceptibility testing was determined by broth microdilution. In addition, a comparative analysis of these ICEs was conducted with bioinformatic tools, and the transfer abilities of these ICEs were confirmed by conjugation. Four ICEHpa1 variants ICEGpa1818, ICEGpa1808, ICEGpa1807 and ICEGpa1815 with different resistance gene profiles were characterized, and their hosts showed different resistance spectrums. All ICEs shared the same backbone and were inserted into the tRNALeu site, and all resistance regions were inserted into the same target site between the accessory and integration regions. This study analyzed complete sequences of ICEs from the ICEHpa1 family and identified novel T4SS and insertion element ISGpa2. Diverse resistance genes extensively exist in these ICEs, serving as a reservoir for resistance genes and facilitating their dissemination.